Technology and talent strategies for sustainable smart cities : digital futures - Dadwal, Sumesh Singh; Jahankhani, Hamid; Bowen, Gordon; Nawaz, Imad Yasir (Emerald Publishing Limited, 2023)
Governments, communities, and developers are considering the use of ICT, renewable energies, and a host of other technologies to build smart cities that meet the economic, social, environmental, and cultural needs of the present as well as the future. However, are our cities ready for this technological shift? Can we put expansion behind us and focus on sustainability and re-generatability? Are the technologies themselves enough to create real impact and an overall healthier planet? Acknowledging the smart cities phenomenon not as a future goal but as an active part of our present, this book critically examines the strategies, business models, practices, tools, and actions needed to ensure that smart cities deliver the solutions they promise.